Legal Aspects of the Financing of Religious Groups in Spain - Celador Angón, Óscar (The Age of Human Rights Journal, 2014)
The purpose of this paper is to analyze the Spanish public polices in the financing of churches and religious organizations. According to this approach, and taking in account that the Spanish legal frame lack of a common regulation for all religious groups, this paper aims to provide analysis of the following issues: the constitutional principles of the Spanish political system relevant to the religious freedom, the cooperation agreements between the State and the religious groups, and the economic and fiscal regime of the Catholic Church and the religious minorities.